Using Western movies to enhance cross-cultural understanding among English literature students - Budi Purnomo (Pioneer: Journal of Language and Literature, 2025)
This study investigates how Western movies facilitate students’ cross-cultural understanding in a Cross-Cultural Understanding (CCU) course within an English Literature program in Indonesia. Using a qualitative descriptive design, data were collected over four instructional weeks through classroom observations, audio-video recordings of role-plays, and reflective journals. The findings show a clear progression in students’ intercultural learning. Initially, students experienced cultural dissonance when encountering unfamiliar pragmatic features such as direct refusals, sarcasm, and informal teacher-student interaction. With guided scaffolding, they began to reinterpret these behaviours and develop emerging cultural awareness. By the third week, students engaged in comparative reasoning between Western and Indonesian/Javanese norms, which later evolved into perspective-taking in the final week. Reflective journals reveal increased confidence, pragmatic sensitivity, and deeper cultural insight. Overall, the study concludes that Western movies are effective multimodal input for intercultural learning, but their pedagogical value is maximized when paired with structured discussions and reflective tasks.